Inaudible airborne ultrasound affects emotional states in the olfactory bulbectomized rat depression model - Tsugumi Yamauchi; Kou Takahashi; Toshinori Yoshioka; Daisuke Yamada; Yoshio Nakano; Satoka Kasai; Satoshi Iriyama; Kazumi Yoshizawa; Shoichi Nishino; Satoru Miyazaki; Akiyoshi Saitoh (Scientific Reports)
Abstract Recently, exposure to sounds with ultrasound (US) components has been shown to modulate brain activity. However, the effects of US on emotional states remain poorly understood. We previously demonstrated that the olfactory bulbectomized (OBX) rat depression model is suitable for examining the effects of audible sounds on emotionality. Here, we investigated the impact of US exposure on the emotional state of OBX rats. In naive rats, exposure to 100 kHz US for 1 h did not increase the number of c-Fos-positive cells in auditory-related cortical areas, and US, as a tone cue, did not elicit a conditioned fear response in the auditory fear conditioning test. These results indicate that the frequency of 100 kHz is hard to hear for rats. However, US improved hyperemotionality (HE) scores and decreased plasma corticosterone levels in OBX rats, suggesting ameliorative effects on depression-like symptoms and stress. In contrast to HE scores, US exposure did not influence anxiety-like behaviors in the elevated plus maze. In conclusion, we demonstrated that exposure to airborne US can alleviate depressive-like symptoms in the OBX rat depression model. This is the first study to show that exposure to airborne US alone produces changes in emotional states in an animal model.